ChemInform Abstract: Iron‐Catalyzed Three‐Component Tandem Process: A Novel and Convenient Synthetic Route to Quinoline‐2, 4‐Dicarboxylates from Arylamines, Glyoxylic Esters, and α‐Ketoesters. Issue 20 (20th May 2014) - Wei, Wei; Wen, Jiangwei; Yang, Daoshan; Sun, Xuejun; You, Jinmao; Suo, Yourui; Wang, Hua
Abstract The new multicomponent reaction of aromatic amines, glyoxylic esters, and α‐ketoesters provides an attractive approach to a series of functionalized quinoline derivatives with promising unique pharmaceutical, biological, and fluorescence‐labeling applications.